Efficacy and Safety of Sevelamer Carbonate in Chinese Nondialysis Chronic Kidney Disease Patients with Hyperphosphatemia: A Randomized, Double-Blind, Parallel-Group Study - Wei Chen; Hua-Feng Liu; Qin-Kai Chen; Ming-Hui Zhao; Xiao-Nong Chen; Hong Liu; Jian-Xin Wan; Shao-Mei Li; Meng-Hua Chen; Chun Dai; Hong-Bin Shi; Jia-Li Wei; et al. (Kidney Diseases, 2022)
Introduction: Previous studies suggested that sevelamer carbonate is well tolerated with a favorable efficacy and safety profile in both dialysis and nondialysis patients in Europe; however, the efficacy remains controversial, and few studies have examined sevelamer carbonate therapy in other ethnic nondialysis CKD patients. This study assessed the efficacy and safety of sevelamer carbonate in Chinese nondialysis CKD patients with hyperphosphatemia. Methods: The multicenter, randomized, double-blind, parallel group, placebo-controlled, and phase 3 clinical trial enrolled 202 Chinese nondialysis CKD patients with serum phosphorus ≥1.78 mmol/L. Patients were randomly assigned 1:1 to receive sevelamer carbonate (2.4-12 g per day) or placebo for 8 weeks. The primary outcome was the change in serum phosphorous between baseline and week 8. Results: Totally 482 Chinese patients were screened and 202 were randomized (sevelamer carbonate, n=101; placebo, n=101). The mean serum phosphorous decreased significantly in patients treated with sevelamer carbonate compared with placebo (-0.22±0.47 vs. 0.05±0.44 mmol/L, p<0.0001). Significantly (p<0.0001) decreases of serum total cholesterol, low-density lipoprotein cholesterol and calcium-phosphorus (Ca × P) product levels from baseline to week 8 were shown in sevelamer carbonate group compared with placebo group. Serum intact parathyroid hormone (iPTH) was not significantly changed in the sevelamer carbonate group (p=0.83). Patients in the sevelamer carbonate group experienced similar adverse events as the placebo group. Conclusion: Sevelamer carbonate is an effective and well-tolerated phosphate binder in advanced nondialysis CKD Chinese patients with hyperphosphatemia.